Seismic behavior of steel truss and concrete composite shear wall with double X-shaped braces. (15th December 2022) - Xing, Yonghui; Wang, Weiyong; Ou, Ying; Jiang, Xianchun; Al-azzani, Hisham
Abstract: Aiming to enhance the seismic performance and assembly of reinforced concrete (RC) shear walls, a novel steel truss and concrete composite (STCC) shear wall with twin X-shaped braces are proposed. Four STCC shear walls and one RC shear wall were tested under cyclic lateral and constant axial load to determine the effect of the number of channel columns and the addition of a crossbar on the seismic performance of STCC walls, as well as the difference in the seismic performance between the STCC wall and RC wall. Based on the test results, an optimal truss design is presented. Additionally, a comprehensive parametric analysis was carried out on 27 finite element models to investigate the influence of critical factors, such as the axial load ratio, the steel ratio of embedded steel columns, and the volumetric ratio of embedded braces, on the seismic performance of STCC walls. Results indicated that the ductility and the energy dissipation of the STCC shear walls were significantly improved, consequently reducing the number and extension of concrete cracks. Double channel columns could improve the bearing capacity of the STCC walls and provide sufficient support for X-shaped braces. Moreover, adding a crossbar could reduce the stiffness and bearing capacity degradation rate of the wall, but strengthening the connection between the column and the reinforcement inside the bottom foundation is recommended. The axial load ratio and the steel ratio of channel columns had more significant influence on the bearing capacity of STCC walls than the volumetric ratio of embedded braces. Finally, a calculation method is proposed, and the calculated results are in good agreement with the test findings. Highlights: Experimental study on seismic response of steel truss and concrete composite shear wall was presented. Numerical model was established to predict the seismic response of steel truss and concrete composite shear wall. Parametric analysis was conducted on the seismic performance of steel truss and concrete composite shear wall. The optimal truss arrangement is suggested for steel truss and concrete composite shear wall.